Effectiveness and safety of the XEN45 gel stent compared to trabeculectomy in primary open-angle glaucoma: the Gold-Standard Pathway Study - Kaweh Mansouri; Xuemin Gu; Ingeborg Stalmans; Herbert A Reitsamer; Iqbal K Ahmed; Vanessa Vera; Antonio Maria Fea; Earl Randy Craven (BMJ Open Ophthalmology)
Aim To compare the gel stent to trabeculectomy in the Gold-Standard Pathway Study (GPS) patients with primary open-angle glaucoma (POAG).Methods In the GPS, patients with elevated intraocular pressure (IOP) poorly controlled with IOP-lowering medication were randomised (2:1, gel stent:trabeculectomy). Aggregate primary endpoint: patients (%) at month 12 achieving ≥20% IOP reduction from baseline without medication increase, clinical hypotony, vision loss to counting fingers or secondary surgical intervention (SSI). Secondary endpoints included changes in mean IOP and medication count from baseline; postoperative interventions; visual recovery; postoperative complications; and the Symptom and Health Problem Checklist (SHPC-18) questionnaire.Results Of 130 eyes with POAG treated/analysed (gel stent, n=88; trabeculectomy, n=42); 61.4% and 69.0% met the primary endpoint, respectively (p=0.394). At month 12, the change from baseline in mean IOP was statistically greater post-trabeculectomy (by 2.8 mm Hg; p=0.028) than post-gel stent. Postoperative intervention and postoperative complication rates were 39.8% and 75.0% (gel stent) versus 76.2% and 92.9% (trabeculectomy), respectively. Hypotony (IOP ≤6 mm Hg at two consecutive visits) rates were 14.8% (gel stent) and 28.6% (trabeculectomy). Visual recovery was faster/better (per the mean and time to first return to baseline best corrected visual acuity) and SHPC-18-related improvements were greater post-gel stent than post-trabeculectomy.Conclusion Similar proportions of eyes with POAG achieved the primary endpoint post-gel stent and post-trabeculectomy. The mean IOP reduction was statistically greater post-trabeculectomy. The gel stent resulted in fewer postoperative interventions, faster/better visual recovery, favourable patient-reported outcomes and fewer specific adverse events, although more SSIs and IOP elevations were observed.